PENGARUH RETURN ON EQUITY, DEBT TO EQUITY RATIO, DAN CURRENT RATIO TERHADAP RETURN SAHAM (Studi Kasus Pada Perusahaan Sektor Perindustrian yang Tercatat di Bursa Efek Indonesia Periode 2016-2020) - Melinda S. Meliala; Riska Rosdiana (Universitas Mercu Buana, 2023)
This study aims to analyze the effect of Return on Equity, Debt to Equity Ratio, and Current Ratio on Stock Return. The population in this study are industrial sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period with the sample used as many as 13 companies. The sampling method used purposive sampling. The data collection method uses the documentation method, using data in the form of stock prices, net income, equity, total debt, current assets and current liabilities obtained through the websites finance.yahoo.com and idx.co.id. The data analysis method uses the panel data regression analysis method with the help of Eviews 9 software. The results of this study indicate that Return on Equity has a positive effect on stock returns, Debt to Equity Ratio and Current Ratio have no effect on stock returns.